Systematic Review: History of Distribution and Conservation of Family Dipterocarpaceae through Vegetative Propagation - Andi Sukendro; Siti Aisyiyah (Jurnal Silvikultur Tropika, 2023)
Dipterocarpaceae dominate plants of tropical forests, and their wood is exploiting until it's been rare plants. Conservation through generative propagation has several problems, and vegetative propagation then being as an alternative. This study has two purposes that to understand the history of distribution of Dipterocarpaceae and do research about the development of vegetative propagation techniques that apply for Dipterocarpaceae. This study was using a systematic review method. Commonly, vegetative propagation techniques that have been applied are cuttings and culture in vitro but other vegetative techniques have not to use yet. Research on the vegetative propagation of Upuna and Parashorea has not been available. Cutting is the most propagation technique used and has a good effect on several species of Dipterocarpaceae. Culture in vitro techniques have been used for several genus and need further research. Keywords: conservation, dipterocarpaceae, rare tree, systematic review, vegetative propagation